Three-dimensional continuous reticular composite functional material as well as preparation method and application thereof

Through electroless plating, Cu plating layer is formed on the surface of Ti powder and combined with low temperature rapid sintering technology, the problems of low distribution uniformity and efficiency in traditional materials are solved, and a three-dimensional continuous mesh Ti-Cu composite material with high strength and high thermal conductivity is prepared. , suitable for multi-field applications.

CN119162482AActive Publication Date: 2024-12-20HUAZHONG UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411408638.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-20
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The distribution uniformity and efficiency of traditional three-dimensional network structure materials are low, especially at high temperatures, Ti-Cu alloys are prone to chemical reactions, resulting in uneven element distribution and insufficient material performance.

Method used

The electroless plating method is used to form a uniform Cu plating layer on the surface of Ti powder. The stable existence of Cu is achieved by controlling the sintering process, forming a three-dimensional continuous mesh structure, and combining the low-temperature rapid sintering of the discharge plasma system to prepare a high-strength and high thermal conductivity Ti -Cu composite material.

Benefits of technology

It realizes uniform distribution and efficient preparation of metal mesh structures, improves the strength and thermal conductivity of materials, and is suitable for applications in multiple fields, especially in high temperature and biomedicine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162482A_ABST
    Figure CN119162482A_ABST
Patent Text Reader

Abstract

The invention belongs to the related technical field of reticular structure materials, and discloses a three-dimensional continuous reticular composite functional material and a preparation method and application thereof.The preparation method comprises the steps that (1) Ti powder is soaked in a nitric acid solution for 3-5 min and then taken out; (2) the powder obtained in the step (1) is placed in a sensitizing solution to be stirred for 5-10 min and then taken out; (3) putting the powder obtained in the step (2) into an activation solution, stirring for 6-8 minutes, and then taking out; (4) adding the powder obtained in the step (3) into a plating solution, carrying out water bath heating and stirring, then adding 80ml of a formaldehyde solution, supplementing deionized water to 1000ml, and starting chemical plating; and (5) cleaning and drying the powder obtained in the step (4), and sintering to obtain the three-dimensional continuous reticular composite functional material. The preparation difficulty of the metal net structure is greatly reduced, and the efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to mesh structure materials, and more specifically, relates to a three-dimensional continuous mesh composite functional material and a preparation method and application thereof. Background Art

[0002] Titanium is a new type of structural material with excellent comprehensive properties, such as low density (4.5g / cm 3 ), high specific strength and fracture toughness, good fatigue strength and crack propagation resistance, good low-temperature toughness, and excellent corrosion resistance. At the same time, the working temperature of some titanium alloys is about 550°C, and it is expected to reach a maximum of 700°C. Therefore, titanium alloys are increasingly used in industrial sectors such as aviation, aerospace, chemical industry, and shipbuilding. About 80% of titanium production is used in the aerospace industry. For example, in the United States, titanium accounts for about 1% of the fuselage structural materials of the B-21 bomber, mainly used to manufacture the fuselage, wings, skins, and load-bearing components. For the F-15 fighter structural materials, titanium alloys occupy a capacity of 7,000 kg, which is about 34% of the weight of the fuselage structure.

[0003] The Cu element has the advantage of excellent toughness. Cu is a β-stabilizing element. Part of the copper in the titanium alloy exists in a solid solution state, and the other part forms Ti2Cu or TiCu2 compounds. TiCu2 has thermal stability and plays a role in improving the thermal strengthening of the alloy. Copper, as a common alloying element in biomaterials, has osteogenesis and angiogenesis-promoting functions due to its good antibacterial activity. Alloying pure titanium with Cu can promote the antibacterial properties and biological activity of the matrix. Therefore, the new antibacterial Ti-Cu alloy has become a hot topic around the world today. Generally, it is believed that the antibacterial properties of Ti-Cu alloys are positively correlated with the Cu alloy content. Surface dispersed Ti2Cu phase and leached Cu 2+Contributes to its antibacterial properties. However, mechanical mixing of different filler alloy powders may lead to uneven element distribution, and coating technology is often used as a metallization method to prepare uniform composite materials. By performing chemical plating, electroplating, evaporation, ion plating and other processes on the powder surface, the surface morphology, roughness and mechanical properties of the powder can be improved, thereby improving the uniformity of element distribution and comprehensive performance of the composite material. Hongmei et al. prepared Cu-coated multi-walled carbon nanotubes (MWCNTs) as a reinforcing agent to optimize the mechanical properties of the Zn matrix. The microstructural results showed that MWCNTs were uniformly dispersed in the Zn matrix, and the Cu coating formed a close interface connection between Zn and MWCNTs. In order to overcome the poor wettability and mutual immiscibility of W elements and Cu elements, Li et al. prepared double-layer composite powders of Cu and Ni-coated W powders, and then prepared dense W-Cu composite powders. The use of core-shell structure composite filler metals can achieve uniform distribution of composite filler metal elements. Chemical plating is widely used in the preparation of coating powders for composite materials because it has fewer restrictions on shape and substrate during electroplating. In order to prevent the segregation of Cu elements, improve the interface strength of materials and inhibit bacterial growth, it is necessary to design Cu coating on the surface of Ti powder. What is more noteworthy is that Ti-Cu is very prone to chemical reaction under heating conditions. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a three-dimensional continuous network composite functional material and a preparation method and application thereof, which aims to solve the problems of distribution uniformity and low efficiency of traditional three-dimensional network structure materials.

[0005] To achieve the above object, according to one aspect of the present invention, a method for preparing a three-dimensional continuous network composite functional material is provided, the method comprising the following steps:

[0006] (1) Soak the Ti powder in nitric acid solution for 3-5 minutes and then take it out;

[0007] (2) adding 10 g of stannous chloride to 960 ml of deionized water, then adding 40 ml of a 36% hydrochloric acid solution, and finally adding deionized water to 1 L, stirring until dissolved to obtain a sensitizing solution; then, placing the powder obtained in step (1) in the sensitizing solution, stirring for 5 min-10 min, and then taking it out;

[0008] (3) Take 0.25 g of palladium chloride, add 800 ml of deionized water, then add 10 ml of 36% hydrochloric acid solution, and finally add deionized water to 1 L, stir until dissolved to obtain an activation solution; then, place the powder obtained in step (2) in the activation solution, stir for 6 min-8 min, and then take it out;

[0009] (4) 0.2 g of 2,2'-bipyridine, 0.2 g of potassium ferrocyanide, 50 g of copper sulfate pentahydrate, 15 g of disodium ethylenediaminetetraacetic acid, and 15 g of sodium tartrate tetrahydrate were added to 850 ml of deionized water and stirred until dissolved, and then sodium hydroxide was added to adjust the pH value of the solution to 12 to obtain a plating solution. Then, the powder obtained in step (3) was added to the plating solution, and heated and stirred in a water bath, and then 80 ml of formaldehyde solution was added and the deionized water was supplemented to 1000 ml to start chemical plating;

[0010] (5) The powder obtained in step (4) is cleaned and dried and then sintered to obtain a three-dimensional continuous network composite functional material.

[0011] Furthermore, the sintering conditions in step (5) are: keeping warm at 1300° C. for 3 hours.

[0012] Furthermore, in step (5), the sample powder is sintered using a spark plasma system at a pressure of 40 MPa-200 MPa, a sintering temperature of 500° C.-800° C., and a holding time of 5 min-10 min.

[0013] Furthermore, the mass of Ti powder is 100 g.

[0014] Furthermore, the water bath heating temperature was 43°C.

[0015] Furthermore, the pH value of the plating solution during the chemical plating process is maintained between 11 and 13.5.

[0016] Furthermore, before sintering, the obtained powder was ultrasonically cleaned three times with deionized water and once with alcohol, and then dried in a vacuum drying oven at 70-100° C. for 12 h.

[0017] The present invention also provides a three-dimensional continuous network composite functional material, and the composite functional material is prepared by the preparation method of the three-dimensional continuous network composite functional material as described above.

[0018] The present invention also provides an application of the three-dimensional continuous mesh composite functional material in aerospace, chemical industry and shipbuilding.

[0019] In general, compared with the prior art, the three-dimensional continuous network composite functional material and its preparation method and application provided by the present invention mainly have the following beneficial effects:

[0020] 1. Use chemical plating to modify the powder to achieve the construction of a metal mesh structure. Chemical plating can obtain a layer of metal Cu plating on the surface of Ti powder more evenly, and the thickness of the plating layer can be controlled by the content of chemical reagents, powder particle size and chemical plating time to achieve a mesh metal structure of different thicknesses. This method can be applied to a variety of powders to obtain metal mesh structures of different matrix materials, greatly reducing the difficulty of preparing metal mesh structures and improving efficiency.

[0021] 2. Ti-Cu reacts easily at high temperatures, and different composite materials can be constructed by changing the sintering process. Under ordinary sintering processes, Cu cannot diffuse completely, but under SPS low-temperature rapid sintering, a three-dimensional network structure containing Cu can be formed. At the same time, a stable interface is formed through Ti-Cu, thereby achieving higher strength requirements for composite materials.

[0022] 3. The metal materials prepared by this method can be applied in many fields and scenarios. The antibacterial property of Cu element combined with the high strength and biocompatibility of Ti element makes the metal materials prepared by this method applicable to large fields such as biomedicine and marine engineering; the Cu-containing mesh structure titanium alloy prepared by short-process rapid sintering is expected to make up for the defects of titanium and achieve high heat transfer of titanium-based composite materials, which has broad application prospects in both industrial and military fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flow chart of a method for preparing a three-dimensional continuous network composite functional material provided by the present invention;

[0024] Figure 2 The present invention relates to a schematic diagram of chemical copper plating;

[0025] Figure 3 (a), (b), and (c) are respectively the powder morphology, surface EDS analysis, and XRD diagram after chemical copper plating in Example 1 of the present invention;

[0026] Figure 4 (a) and (b) are schematic diagrams of the SPS sintered morphology and surface EDS analysis of Example 1, respectively;

[0027] Figure 5 is a schematic diagram of the conventional sintered microstructure obtained in Example 2 of the present invention;

[0028] Figure 6 (a) and (b) are schematic diagrams of the SPS sintered morphology and surface EDS analysis of Example 3 of the present invention, respectively;

[0029] Figure 7 (a) and (b) are schematic diagrams of the three-dimensional network structure containing Cu and schematic diagrams of the simulation of its heat transfer path, respectively. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] See also Figure 1 and Figure 2 The present invention provides a method for preparing a three-dimensional continuous mesh composite functional material. The preparation method realizes the stable existence of pure Cu in the Ti-based composite material by controlling the sintering process, thereby meeting the engineering service requirements under some special environments. Titanium alloys have high specific strength and are widely used in various complex environments. However, the thermal conductivity of pure titanium is only about 17W / m·K, which is difficult to be applied in heat transfer materials. However, the thermal conductivity of pure Cu can reach 410W / m·K. By adding copper to the titanium alloy, the excellent performance of Ti-Cu can be realized at the same time. The presence of pure Cu improves the thermal conductivity of the composite material. Ti allows the composite material to adapt to extreme environments due to its excellent specific strength and corrosion resistance. The Ti-Cu reaction at the interface generates compounds to ensure the basic connection strength of the material, giving the titanium-based composite material with a three-dimensional mesh structure of Cu more application possibilities, such as heat pipes on ships and heat transfer vessels in factories.

[0032] At the same time, traditional titanium alloy products rely on forging, casting and rolling of bulk raw materials, and then subsequent processing to achieve the final shape and size, resulting in a large amount of material waste, high manufacturing costs and long delivery time, and there is little research on the construction of internal three-dimensional network structures. In contrast, the present invention uses chemical plating to prepare a new type of Ti composite filler metal coated with a pure Cu layer, prepares a Cu-coated Ti core-shell composite structure powder, and obtains a three-dimensional continuous network composite structure functional material by powder metallurgy, which has great application prospects in many fields.

[0033] The preparation method mainly comprises the following steps:

[0034] Step 1: Place Ti powder in a beaker and ultrasonically clean it with alcohol for 10-15 minutes; then take out the powder and ultrasonically clean it with deionized water (3-5 minutes) three times to remove surface impurities and improve the coating quality. The mass of Ti powder is 100g.

[0035] Step 2, prepare nitric acid solution: take 900ml of deionized water and place it in a beaker, add 100ml of 30% nitric acid to 1L, soak the Ti powder in step 1 in the nitric acid solution for 3-5min and then take it out (to provide coating attachment points and increase Cu-Ti bonding strength), and ultrasonically clean it with deionized water for 3 times.

[0036] Step 3, prepare a sensitizing solution: take 10g of stannous chloride, add 960ml of deionized water, then add 40ml of 36% hydrochloric acid solution, and finally add deionized water to 1L, and stir until dissolved; place the powder obtained in step 2 in the sensitizing solution and stir for 5-10min, then take it out (to provide activation sites for chemical plating and enhance bonding strength), and wash it once with deionized water.

[0037] Step 4, prepare activation solution: take 0.25g of palladium chloride, add 800ml of deionized water, then add 10ml of 36% hydrochloric acid solution, and finally add deionized water to 1L, stir until dissolved; place the powder obtained in step 3 in the activation solution and stir for 6-8min before taking it out (to improve the adhesion between the powder and the coating).

[0038] Step 5, prepare the plating solution: 0.2g of 2,2'-bipyridine, 0.2g of potassium ferrocyanide, 50g of cupric sulfate pentahydrate, 15g of disodium ethylenediaminetetraacetic acid, 15g of sodium tartrate tetrahydrate, add 850ml of deionized water and stir until dissolved, then add sodium hydroxide to adjust the pH value of the solution to 12, add the powder from step 4 to the plating solution, heat in a water bath at 43°C and stir, finally add 80ml of formaldehyde solution and add deionized water to 1000ml to start chemical plating, and the pH value must be kept between 11-13.5 during the chemical plating process.

[0039] Step 6: After filtering the powder obtained in step 5, ultrasonically clean it three times with deionized water and once with alcohol, and then dry it in a vacuum drying oven at 70-100° C. for 12 hours.

[0040] Step 7: By controlling different sintering processes, different structures can be built to obtain three-dimensional continuous network composite functional materials. Method 1 of the two sintering methods: conventional sintering, heat preservation at 1300℃ for 3h; Method 2: sintering the sample powder using a spark plasma system, pressure 40-200MPa, sintering temperature 500-800℃, and heat preservation time 5-10min.

[0041] The present invention also provides a three-dimensional continuous network composite functional material, and the composite functional material is prepared by the preparation method of the three-dimensional continuous network composite functional material as described above.

[0042] The present invention also provides an application of the three-dimensional continuous mesh composite functional material in aerospace, chemical industry and shipbuilding.

[0043] The present invention is further described in detail below with reference to specific embodiments.

[0044] Embodiment 1:

[0045] Embodiment 1 of the present invention comprises the following steps:

[0046] Step 1, weigh 100g Ti powder and place it in a beaker, and ultrasonically clean it with alcohol for 15min; then take out the powder and ultrasonically clean it with deionized water (5min) three times to remove surface impurities and improve the coating quality.

[0047] Step 2, add 100 ml of 30% nitric acid into 900 ml of deionized water, place the powder obtained in step 1 in the solution, stir for 3 minutes, take it out, and ultrasonically clean it with deionized water for 3 times.

[0048] Step 3, take 10g of stannous chloride, add 960ml of deionized water, then add 40ml of 36% hydrochloric acid solution, and stir until dissolved; place the powder obtained in step 2 in the sensitizing solution, stir for 5min, take out, and wash once with deionized water.

[0049] Step 4, take 0.25 g of palladium chloride, add 990 ml of deionized water, then add 10 ml of 36% hydrochloric acid solution, and stir until dissolved; place the powder obtained in step 3 in the activation solution, stir for 8 minutes, and then take it out.

[0050] Step 5, take 0.2g of 2,2'-bipyridine, 0.2g of potassium ferrocyanide, 50g of cupric sulfate pentahydrate, 15g of disodium ethylenediaminetetraacetic acid, and 15g of sodium tartrate tetrahydrate, add 850ml of deionized water and stir until dissolved, then add sodium hydroxide to adjust the pH value of the solution to 12, add the powder from step 4 to the plating solution, heat it in a water bath to 43°C and stir, finally add 80ml of formaldehyde solution and add deionized water to 1000ml to start chemical plating, and keep the pH value at 12 during the chemical plating process (by adding NaOH).

[0051] Step 6, after filtering the powder obtained in step 5, ultrasonically clean it three times with deionized water, clean it once with alcohol, and then dry it in a vacuum drying oven at 70° C. for 12 hours.

[0052] Step 7: Sinter the sample powder using a spark plasma system at a pressure of 50 MPa, a sintering temperature of 700° C., and a holding time of 5 min. The sample is taken out to obtain a three-dimensional metal mesh structure material.

[0053] See also Figure 3It can be clearly observed that Cu uniformly wraps the core Ti, and a core-shell structure titanium-based composite powder is obtained. XRD analysis shows that there is a lot of pure Cu on the Ti surface after chemical plating. Figure 4 , it can be seen that the Cu element forms a continuous network structure inside the material.

[0054] Embodiment 2:

[0055] Embodiment 2 of the present invention comprises the following steps:

[0056] Step 1, using the copper-plated powder in Example 1 for conventional sintering, encapsulating the powder, and cold pressing.

[0057] Step 2: conventional pressureless sintering with a heating rate of 5°C / min and keeping at 1300°C for 3h to achieve complete diffusion of Cu element. Figure 5 .

[0058] Embodiment 3:

[0059] The copper-plated powder in Example 1 was used for spark plasma sintering at a pressure of 50 MPa, a sintering temperature of 650°C, and a holding time of 5 min. The sample was taken out to obtain a three-dimensional metal mesh structure material. By SEM contrast comparison, lowering the sintering temperature can effectively reduce the reaction between Cu and Ti, thereby allowing more pure copper to exist in the mesh structure, thereby preparing a Ti-based composite material containing a Cu mesh, see Figure 6 shown.

[0060] According to the above examples, the doping of Cu mesh in Ti has been realized, and the subsequent process can be optimized on this basis. Through the above examples, it can be found that lowering the sintering temperature and increasing the sintering pressure can obtain higher quality Cu-containing three-dimensional mesh titanium-based composite materials. Due to the limitations of the current experimental conditions, the optimal process preparation has not been achieved, so a simulation analysis of the thermal conductivity of the Cu mesh structure in the Ti-based composite material was carried out. It can be seen that the interconnected Cu structure provides an effective path for the efficient heat transfer of the Ti-based composite material. When the powder particle size of Ti is 60um and the chemically plated Cu layer is 3um, the theoretical thermal conductivity of the titanium-based composite material can reach 79W / m·K through simulation, see Figure 7 .

[0061] Embodiment 4:

[0062] Embodiment 4 of the present invention comprises the following steps:

[0063] Step 1: First, weigh 100 g of Ti powder into a beaker, add 300 ml of anhydrous ethanol and perform ultrasonic cleaning for 10 min. Take out the obtained powder, and then use deionized water to ultrasonically clean it 3 times, each time for 5 min.

[0064] Step 2, add 100 ml of 30% nitric acid into 900 ml of deionized water, place the powder obtained in step 1 in the obtained solution, stir for 3 minutes, take out, and ultrasonically clean it with deionized water for 3 times.

[0065] Step 3, add 10g of stannous chloride to 960ml of deionized water, then add 40ml of 36% hydrochloric acid solution, stir until dissolved to obtain a sensitized solution; place the powder obtained in step 2 in the sensitized solution, stir for 5min, then take it out and wash it once with deionized water.

[0066] Step 4, take 0.25 g of palladium chloride, add 990 ml of deionized water, then add 10 ml of 36% hydrochloric acid solution, stir until dissolved to obtain an activation solution; place the powder obtained in step 3 in the activation solution, stir for 8 minutes and then take it out.

[0067] Step 5, take 0.1g of 2,2'-bipyridine, 0.1g of potassium ferrocyanide, 25g of copper sulfate pentahydrate, 25g of disodium ethylenediaminetetraacetic acid, and 15g of sodium tartrate tetrahydrate, add 960ml of deionized water and stir until dissolved, then add sodium hydroxide and adjust the pH value of the solution to 12 to obtain a plating solution, add the powder obtained in step 4 to the plating solution, heat it in a water bath to 43°C and stir, finally add 40ml of formaldehyde solution to start chemical plating, and keep the pH value at 12 during the chemical plating process.

[0068] Step 6, after filtering the powder obtained in step 5, ultrasonically clean it three times with deionized water, clean it once with alcohol, and then dry it in a vacuum drying oven at 60° C. for 12 hours.

[0069] Step 7: Sinter the obtained powder using a spark plasma system to obtain a three-dimensional metal network structure material. The sintering conditions are: pressure of 50 MPa, sintering temperature of 700° C., and holding time of 5 min.

[0070] Figure 3 This is the EDS spectrum of the Ti powder morphology after chemical copper plating and the distribution of Cu elements on the surface. It can be clearly observed that Cu uniformly wraps the core Ti to obtain a core-shell structured titanium-based composite powder. Figure 4 The sintered morphology of the core-shell structure composite powder obtained after SPS. It can be seen that the Cu element forms a continuous network structure inside the material.

[0071] Example 5

[0072] Embodiment 5 of the present invention comprises the following steps:

[0073] Step 1, first weigh 100 g of Ti powder into a beaker, add 300 ml of anhydrous ethanol and ultrasonically clean it for 10 minutes, take out the powder after ultrasonic cleaning and then ultrasonically clean it with deionized water for 3 times, each time for 5 minutes.

[0074] Step 2, add 100 ml of 30% nitric acid into 900 ml of deionized water, place the powder obtained in step 1 in the obtained solution, stir for 5 minutes, take out, and ultrasonically clean it with deionized water for 3 times.

[0075] Step 3, add 10g of stannous chloride to 960ml of deionized water, then add 40ml of 36% hydrochloric acid solution, stir until dissolved to obtain a sensitized solution; place the powder obtained in step 2 in the sensitized solution, stir for 5min, then take it out and wash it once with deionized water.

[0076] Step 4, add 0.5 g of palladium chloride to 990 ml of deionized water, then add 10 ml of 36% hydrochloric acid solution, stir until dissolved to obtain an activation solution; place the powder obtained in step 3 in the activation solution, stir for 10 minutes and then take it out.

[0077] Step 5, take 0.4g of 2,2'-bipyridine, 0.4g of potassium ferrocyanide, 100g of copper sulfate pentahydrate, 100g of disodium ethylenediaminetetraacetic acid, 60g of sodium tartrate tetrahydrate, add 840ml of deionized water and stir until dissolved, then add sodium hydroxide to adjust the pH value of the obtained solution to 12 to obtain a plating solution, add the powder obtained in step 4 to the plating solution, heat it in a water bath to 43°C and stir, finally add 160ml of formaldehyde solution to start chemical plating, and keep the pH value at 12.5 during the chemical plating process.

[0078] Step 6, after filtering the powder obtained in step 5, ultrasonically clean it three times with deionized water, clean it once with alcohol, and then dry it in a vacuum drying oven at 40° C. for 12 hours.

[0079] Step 7: Sinter the obtained powder using a spark plasma system to obtain a three-dimensional metal network structure material. The sintering conditions are: pressure of 50 MPa, sintering temperature of 650° C., and holding time of 5 minutes.

[0080] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional continuous network composite functional material, characterized in that: The method comprises the following steps: (1) Soak the Ti powder in nitric acid solution for 3-5 minutes and then take it out; (2) adding 10 g of stannous chloride to 960 ml of deionized water, then adding 40 ml of a 36% hydrochloric acid solution, and finally adding deionized water to 1 L, stirring until dissolved to obtain a sensitizing solution; then, placing the powder obtained in step (1) in the sensitizing solution, stirring for 5 min-10 min, and then taking it out; (3) Take 0.25 g of palladium chloride, add 800 ml of deionized water, then add 10 ml of 36% hydrochloric acid solution, and finally add deionized water to 1 L, stir until dissolved to obtain an activation solution; then, place the powder obtained in step (2) in the activation solution, stir for 6 min-8 min, and then take it out; (4) 0.2 g of 2,2'-bipyridine, 0.2 g of potassium ferrocyanide, 50 g of copper sulfate pentahydrate, 15 g of disodium ethylenediaminetetraacetic acid, and 15 g of sodium tartrate tetrahydrate were added to 850 ml of deionized water and stirred until dissolved, and then sodium hydroxide was added to adjust the pH value of the solution to 12 to obtain a plating solution. Then, the powder obtained in step (3) was added to the plating solution, and heated and stirred in a water bath, and then 80 ml of formaldehyde solution was added and the deionized water was supplemented to 1000 ml to start chemical plating; (5) The powder obtained in step (4) is cleaned and dried and then sintered to obtain a three-dimensional continuous network composite functional material.

2. The method for preparing a three-dimensional continuous network composite functional material according to claim 1, characterized in that: The sintering conditions in step (5) are: keeping warm at 1300°C for 3 hours.

3. The method for preparing the three-dimensional continuous network composite functional material according to claim 1, characterized in that: In step (5), the sample powder is sintered by a spark plasma system at a pressure of 40 MPa-200 MPa, a sintering temperature of 500° C.-800° C., and a holding time of 5 min-10 min.

4. The method for preparing a three-dimensional continuous network composite functional material according to claim 1, characterized in that: The mass of Ti powder is 100g.

5. The method for preparing the three-dimensional continuous network composite functional material according to claim 1, characterized in that: The water bath was heated to 43°C.

6. The method for preparing a three-dimensional continuous network composite functional material according to any one of claims 1 to 5, characterized in that: During the chemical plating process, the pH value of the plating solution is maintained between 11-13.

5.

7. The method for preparing the three-dimensional continuous network composite functional material according to claim 1, characterized in that: Before sintering, the obtained powder was ultrasonically cleaned three times with deionized water and once with alcohol, and then dried in a vacuum drying oven at 70-100°C for 12 h.

8. A three-dimensional continuous network composite functional material, characterized in that: The composite functional material is prepared by the method for preparing a three-dimensional continuous network composite functional material according to any one of claims 1 to 7.

9. Application of the three-dimensional continuous network composite functional material according to any one of claims 1 to 7 in aerospace, chemical industry and shipbuilding.

Citation Information

Patent Citations

  • Carbon fiber reinforced titanium alloy compound material and preparation method thereof

    CN102912263A

  • Lost foam casting method of three-dimensional network ceramic-iron-based composite material

    CN107398544A

  • Negative Poisson's ratio three-dimensional composite structure unit cell for bone implantation and bone fixing implant

    CN114748214A

  • Wear resistant composite material

    JP1994212323A